Pengaruh pemberian larutan daun tempuyung (sonchus arvensis) dalam air minum terhadap performa ayam broiler - Ludgardis Wea Wona; Ni Putu F. Suryatni; Jhonas F. Theedens (Jurnal Peternakan Lahan Kering, 2019)
The purpose of this study was to evaluate the effect of tempuyung leaf solution in drinking water on ration consumption, daily body weight gain and feed convertion of broiler. The material used is Chicken Day Old Chick (DOC) strain CP 707 as much as 96 production of PT Charoen Pokphand Indonesia. This study used Completely Randomized Design (RAL) 4 treatments with six replications. The treatments were drinking water contain different level of lemputuyng leaf solution namely: R0: 0 ml; R1: 10 ml; R2: 20 ml and R3:30 ml. The parameters measured were ration consumption, body weight gain and feed conversion. The result research showed that ration consumption (g/day) was 97,59 (R0); R1 97,26, R2 96,68, R3 95,86 , while daily body weight gain (g/day) was 45.51 (R0); 46.16 (R1); 45.13 (R2) and 43.82 (R3). Feed conversionwas 2.13 (R0); 2.13 (R1);2,15 (R2) and 2.21 (R3). Statistical analysis showed that the treatment had no effect onparameter measured. It can be concluded that ration consumption, daily weight gain and feed conversion of broiler not depend on lempuyung solution provifing in drinking water.